Effective Leadership to Alter School Food Environments and Improve Public Health - Philip R. McNab (University of North Florida, 2012)
Multiple studies show that many children and adolescents in the United States are overweight or at risk for overweight; moreover, the numbers are still rising. Contributing to the problem is the fact that schoolchildren, on average, are eating too much fast food and well below the recommended amounts offruits and vegetables. From a public health perspective, these are severe problems, as they have been associated with diseases such as heart stroke and heart disease. Not surprisingly, school food environments, which are often saturated with low-nutrient energy-dense foods, are not helping matters and need to be altered. Interventions involving nutrition education or environmental changes have yielded positive outcomes overall, but more innovative and multifaceted approaches are needed. School gardens may be one such approach. Most importantly, to overcome funding concerns and other obstacles, schools need strong and effective leadership, and they need to follow the eight steps delineated by John Kotter. By doing this, public health educators and school staff can change school food environments and enhance the lives of millions of children nationwide.